Exploring disability : a sociological introduction - Barnes, Colin, 1946-; Mercer, Geof.; Shakespeare, Tom. (Malden, Mass : Polity Press, 1999)
This book is about: Understanding disability; Sociological approaches to chronic illness and disability; Enter disability theory; Disabling barriers; ...
Keywords: Sociology; Sociology of disability; Handicapped -- Research; Handicapped -- Government policy